Time-temperature Thresholds and Safety Factors for Thermal Hazards from Radiofrequency Energy above 6 GHz - Foster, Kenneth R. (Health Phys, 2021)
Two major sets of exposure limits for radiofrequency (RF) radiation, those of the International Commission on Nonionizing Radiation Protection (ICNIRP 2020) and the Institute of Electrical and Electronics Engineers (IEEE C95.1–2019), have recently been revised and updated with significant changes in limits above 6 GHz through the millimeter wave (mm-wave) band (30–300 GHz). This review compares available data on thermal damage and pain from exposure to RF energy above 6 GHz with corresponding data from infrared energy and other heat sources and estimates safety factors that are incorporated in the IEEE and ICNIRP RF exposure limits. The benchmarks for damage are the same as used in ICNIRP IR limits: minimal epithelial damage to cornea and first-degree burn (erythema in skin observable within 48 h after exposure). The data suggest that limiting thermal hazard to skin is cutaneous pain for exposure durations less than ≈20 min and thermal damage for longer exposures. Limitations on available data and thermal models are noted. However, data on RF and IR thermal damage and pain thresholds show that exposures far above current ICNIRP and IEEE limits would be required to produce thermally hazardous effects. This review focuses exclusively on thermal hazards from RF exposures above 6 GHz to skin and the cornea, which are the most exposed tissues in the considered frequency range.